Cost-benefit relationship of the implementation of productive technologies in the cow-calf system - Torres Aburto, Víctor Fernando; Severino Lendechy, Víctor Hugo; Gutiérrez Cervantes, Adrián; Itza Ortiz, Mateo; Espinosa Ortiz, Valentín Efrén; Ahuja Aguirre, Concepción (Acta Universitaria, 2025)
The objective of this work evaluated the cost-benefit relationship of the implementation of productive technologies in a livestock production unit dedicated to the production of calves for supply. The technologies evaluated were: pregnancy diagnosis, evaluation of stallions, nutritional supplementation and health program. The results of the application of said technologies were observed in the following indicators: andrological evaluation, fertility rate, interval between calving, birth rate, weaned calves, and cost-benefit. Andrological evaluation indicated an improvement in the semen quality of bulls. Fertility rate, birth rate and weaned calves increased 33.5±1.3, 33.6±1.3 and 13.8±1.0 %, respectively. There was a reduction in interval between calving of 142.5±12.75 days, and a cost-benefit relationship of 1.00 was obtained. In conclusion, the cost-benefit relationship did not imply an economic advantage. However, the implementation of productive technologies presented a gradual increase in the reproductive and productive variables, managing to recover the investment made in the study period.